2015
DOI: 10.1016/j.bmcl.2014.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Structural measurements and cell line studies of the copper–PEG–Rifampicin complex against Mycobacterium tuberculosis

Abstract: The bacterium responsible for tuberculosis is increasing its resistance to antibiotics resulting in new multidrug-resistant Mycobacterium tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB). In this study, several analytical techniques including NMR, FT-ICR, MALDI-MS, LC-MS and UV/Vis are used to study the copper-Rifampicin-Polyethylene glycol (PEG-3350) complex. The copper (II) cation is a carrier for the antibiotic Rifampicin as well as nutrients for the bacterium. The NIH-NIAID cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…6b). Our choice of Cu was based on evidence of its anti-TB potential (Festa R.A. et al, 2014;Neyrolles O. et al, 2015;Speer A. et al, 2013;Wolschendorf F. et al, 2011) as well as demonstrated in vitro synergy with other known anti-TB drugs (Manning T. et al, 2015a;Speer A. et al, 2013). POA has been explored as an anti-TB candidate since it is considered a prodrug of pyrazinamide (PZA), a current first line TB drug experiencing drug resistance from Mtb (Durham P.G.…”
Section: Aerosolized Mofs For Pulmonary Therapymentioning
confidence: 99%
“…6b). Our choice of Cu was based on evidence of its anti-TB potential (Festa R.A. et al, 2014;Neyrolles O. et al, 2015;Speer A. et al, 2013;Wolschendorf F. et al, 2011) as well as demonstrated in vitro synergy with other known anti-TB drugs (Manning T. et al, 2015a;Speer A. et al, 2013). POA has been explored as an anti-TB candidate since it is considered a prodrug of pyrazinamide (PZA), a current first line TB drug experiencing drug resistance from Mtb (Durham P.G.…”
Section: Aerosolized Mofs For Pulmonary Therapymentioning
confidence: 99%
“…For example, the polyethylene glycol (PEG-PLGA/magnetite (γ-Fe 2 O 3 )) co-assembled with the antibiotic cotrimoxazole resulted in an excellent delivery system for the release of a drug via an external magnetic impulse [159]. Similarly, Au-conjugated PLGA-PEG-succinate-PEG-PLGA NPs assembled with Rf exhibited a time-controlled release useful for a long-term personalized therapy [160] and, similarly, Rf-Cu complexes were assembled in several structures with PEGs of different length [161].…”
Section: Delivery Systems For Antibacterial Compounds In Tbmentioning
confidence: 99%